Verified methods for computing Pareto sets: General algorithmic analysis - Tóth, Boglárka G.; Kreinovich, Vladik (Zielona Góra: Uniwersytet Zielonogórski)
In many engineering problems, we face multi-objective optimization, with several objective functions f1, . . . , fn. We want to provide the user with the Pareto set - a set of all possible solutions x which cannot be improved in all categories. The user should be able to select an appropriate trade-off between, say, cost and durability. We extend the general results about (verified) algorithmic computability of maxima locations to show that Pareto sets can also be computed.
Keywords: multi-objective optimization; Pareto set; verified computing